The Differential Effects of pp120 (Ceacam 1) on the Mitogenic Action of Insulin and Insulin-Like Growth Factor 1 Are Regulated by the Nonconserved Tyrosine 1316 in the Insulin Receptor - Soni, Payal (American Society for Microbiology, 2000)
pp120 (Ceacam 1) undergoes ligand-stimulated phosphorylation by the insulin receptor, but not by the insulin-like growth factor 1 receptor (IGF-1R). This differential phosphorylation is regulated by the C terminus of the β-subunit of the insulin receptor, the least conserved domain of the two receptors. In the present studies, deletion and site-directed mutagenesis in stably transfected hepatocytes derived from insulin receptor knockout mice (IR(−/−)) revealed that Tyr(1316), which is replaced by the nonphosphorylatable phenylalanine in IGF-1R, regulated the differential phosphorylation of pp120 by the insulin receptor. Similarly, the nonconserved Tyr(1316) residue also regulated the differential effect of pp120 on IGF-1 and insulin mitogenesis, with pp120 downregulating the growth-promoting action of insulin, but not that of IGF-1. Thus, it appears that pp120 phosphorylation by the insulin receptor is required and sufficient to mediate its downregulatory effect on the mitogenic action of insulin. Furthermore, the current studies revealed that the C terminus of the β-subunit of the insulin receptor contains elements that suppress the mitogenic action of insulin. Because IR(−/−) hepatocytes are derived from liver, an insulin-targeted tissue, our observations have finally resolved the controversy about the role of the least-conserved domain of insulin and IGF-1Rs in mediating the difference in the mitogenic action of their ligands, with IGF-1 being more mitogenic than insulin.